Gageures de la Vision 2020 pour l'Amérique Latine: l'alimentation et l'agriculture depuis 1970 - Garrett, James L. (International Food Policy Research Institute, 1997)
In recent years, the countries of Latin America have made radical changes in their development strategies, including decentralization of government, privatization, and deregulation of markets. These changes have already affected the livelihoods of millions of the region’s inhabitants and promise to reshape the region’s food and agricultural system well into the 21st century. How will these changes help the countries of the region confront the challenges to achieving the 2020 Vision for Latin America, a vision of a world where wealth is fairly distributed; where there is no hunger, extreme poverty, or malnutrition; and where resource use benefits the generations of tomorrow as well as the people of today? In this brief, the authors review the current challenges faced by these countries and offer some suggestions for achieving the 2020 vision for Latin America.